The alternative pathway: Factors influencing middle-income parents to choose homeschooling - Kumar, Menaga; Singh, Gurdip Kaur Saminder; Rahim, Rabiha Maya Adiera Binti Ab (Edelweiss Applied Science and Technology, 2024)
Given that Malaysia is still a developing country with a predominantly middle-income population, understanding the dynamics of homeschooling within this economic context was critical. The objective of this study was therefore to explore the factors influencing middle-income Malaysian parents’ decisions to homeschool their children. This study which was a qualitative case-study, was conducted through in-depth interviews with three middle-income parents’ whose children were currently homeschooling in Malaysia. The self-designed instrument achieved a Kappa score of .74, ensuring reliability of instrument for data collection. Braun and Clarke’s (2006) thematic analysis approach integrated by Miles et al.’s (2013) three-cycle analytical coding was utilized in analyzing the data. The results from the in-depth interviews revealed four major themes which discussed factors influencing middle-income Malaysian parents’ decisions to homeschool their children. Flexibility and individualized learning, discontent with traditional schooling, children’s ability and disparity in classroom instructions and cultural independence have led many middle-income parents to explore home-schooling as an alternative educational option. The findings in this study uncovered that many parents perceived the home environment as a perfect setting for education. This study has practical implications as it highlighted the importance of creating a more inclusive and effective educational environment within the traditional school environment, hence decreasing the need for parents to choose homeschooling as an educational option.